Synthesis New Liquid Selective Electrodes of Ciprofloxacin Hydrochloride for Determination Ciprofloxacin in Pure form and Pharmaceuticals Preparation. - Baghdad Science Journal (مجلة بغداد للعلوم, 2017)
New membrane electrodes for determination of ciprofloxacin hydrochloride were prepared depending on ciprofloxacin hydrochloride - phosphotungstic acid (CFH-PT) as an active material and these electrodes were made with three plasticizers: Di-octylphenylphosphonate(DOPH), Di-butyl phosphate (DBP)Tri-n-butyl phosphate(TBP), in PVC matrix. One of the ciprofloxacin electrodes was gave Nernstian slope equal to 57.21 mV/ decade for DOPH membrane with concentration range from 1.5×10-5 to1.0×10-1 M, and detection limit equal to 1.5×10-6 M .Lifetime was 93 days. Non- Nernstian responses equal to 39.40 and 30.70 mV/ decade for membranes DBP, TBP, respectively. These electrodes were gave concentration range from 1.0× 10-5 to 1.0×10-2 and from 4.0×10-5 to 1.0×10-2 M,respectively. Detection limits were 7.0×10-6, and 1.7×10-6M, respectively. Lifetimes were 5,2 days, respectively. Also selectivity, influence of PH and samples analysis of ciprofloxacin in a pharmaceutical preparations were studied.